The comparative analysis of the effectiveness of stimulation of liver regeneration by bone marrow cells and total RNA of these cells - Z. Z. Gonikova; A. O. Nikolskaya; L. A. Kirsanova; M. Yu. Shagidulin; N. A. Onishchenko; V. I. Sevastianov (Вестник трансплантологии и искусственных органов)
Extensive liver resection (ELR), performed in a number of surgical operations, refers to a critical injury, which necessitates the improvement of methods of therapy of acute post-resection liver failure.Aim: to compare the effectiveness of stimulation of regenerative processes in the liver residue after ELR (60–70%) by intraperitoneal administration of lysed aspirate bone marrow cells (BMCs) and total RNA (tRNA) isolated from BMCs.Materials and methods. This work was performed on 175 rats-male Wistar breed 250–300 g, on 75 of which under the inhalation anesthesia it was reproduced the model of the ELR in three groups of experiments: group 1 – control (administration of isotonic solution after ELR), group 2 – in 3–5 hours after ELR the tRNA from BMCs was intraperitoneally injected at a dose of 30 μg/100 g, group 3 – in 3–5 hours after ELR BMCs was administered intraperitoneally at a dose of 30–35 × 106 cells per rat. Comparative studies of the restorative processes in the liver after the ELR in the three groups were carried out by dynamic control of the mitotic activity of hepatocytes in the liver residue, cytolytic enzymes, total bilirubin and total serum protein, as well as the liver residue (mass) weight.Results. The tRNA from BMCs and BMCs in the indicated doses prevent the risk of the development of lethal outcomes, and also contribute to an earlier (by 10–14 days) normalization of the functional indices of hepatic homeostasis. However, the tRNA from BMCs, compared with BMCs, has a stronger stimulating effect on the recovery processes: it promotes earlier intensification of mitotic activity of hepatocytes and provides a higher rate of recovery of liver mass.Conclusion. For the induction of recovery processes in the liver residue after ELR, the preference should be given to the tRNA from BMCs.